2020
DOI: 10.3389/fpsyt.2020.00147
|View full text |Cite
|
Sign up to set email alerts
|

Self-Criticism and Personality Functioning Predict Patterns of Symptom Change in Major Depressive Disorder

Abstract: Aim of the study was to identify patient variables that predict specific patterns of symptom course during and after hospital treatment for major depressive disorder (MDD). In a sample of 518 patients, four pairs of clinically relevant patterns of symptom change were contrasted. The time points of measurement were admission, discharge, 3 and 12 month after discharge. CATREG was used to identify the best sets of predictors from 28 variables. A greater reduction in self-criticism during hospital treatment was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…We found a bifactor structure with one general depression factor, and two lower order factors indicating (a) self-criticism (i.e., “guilty feelings,” “self-dislike,” “self-criticism,” and “worthlessness”) and (b) somatic symptoms (i.e., “changes in sleeping pattern,” “changes in appetite,” “tiredness or fatigue”) as specific subfactors of depression in this patient group. These findings accord with previous research indicating that self-critical cognitions may play a central role in maintaining CD (Blatt et al, 1982; Dent & Teasdale, 1988; Hawley et al, 2014; Luyten et al, 2007; Mongrain & Leather, 2006; Zeeck et al, 2020) and should be specifically targeted in treatment (Werner et al, 2019). Previous research has been inconsistent with regard to how different treatments affect self-criticism.…”
supporting
confidence: 91%
“…We found a bifactor structure with one general depression factor, and two lower order factors indicating (a) self-criticism (i.e., “guilty feelings,” “self-dislike,” “self-criticism,” and “worthlessness”) and (b) somatic symptoms (i.e., “changes in sleeping pattern,” “changes in appetite,” “tiredness or fatigue”) as specific subfactors of depression in this patient group. These findings accord with previous research indicating that self-critical cognitions may play a central role in maintaining CD (Blatt et al, 1982; Dent & Teasdale, 1988; Hawley et al, 2014; Luyten et al, 2007; Mongrain & Leather, 2006; Zeeck et al, 2020) and should be specifically targeted in treatment (Werner et al, 2019). Previous research has been inconsistent with regard to how different treatments affect self-criticism.…”
supporting
confidence: 91%
“…While patient samples and response rates are comparable between inpatient and day-clinic settings (Zeeck et al, 2015), not all patients respond equally well to treatment. Heterogeneous treatment responses have been well documented for outpatient treatment of depression (Kaiser et al, 2022), but several studies showed that the phenomenon also translates to other mental disorders (e.g., Altmann et al, 2020;Senger et al, 2021) and inpatient treatment settings (Hartmann et al, 2018;Zeeck et al, 2020). To improve response rates, reduce relapse rates, and avoid exposing patients to multiple treatment failures, researchers and clinicians have been interested in learning about risk factors of treatment, adapting treatments to patient needs and understanding which treatment is best suited to an individual patient (e.g., Delgadillo, 2021;Delgadillo & Lutz, 2020;Zeeck et al, 2013).…”
Section: Predicting Treatment Response Using Machine Learning: a Regi...mentioning
confidence: 99%
“…Other psychological and psychiatric variables that have shown associations with treatment response (for depression) are among others chronicity, psychosocial functioning, psychological and physical comorbidity, personality, childhood adversity and recent trauma, cognitive deficits, and coping resources (Kessler et al, 2017;Maj et al, 2020). For inpatient treatment specifically, comorbid (mental) disorders, personality, chronicity, and patient motivation have been found to impact response (Beutel & Bleichner, 2011;Herzog et al, 2021;Zeeck et al, 2016Zeeck et al, , 2020. However, the number of studies empirically addressing this question in inpatient settings is sparse.…”
Section: Predicting Treatment Response Using Machine Learning: a Regi...mentioning
confidence: 99%
“…Specific personality disorders as well as dimensional measures of levels of personality are related to health-related outcomes ( Dokucu and Cloninger, 2019 ; Sinnaeve et al, 2021 ). Deficits in personality functioning appear to have a negative impact on disease progression and adherence ( Collier et al, 1999 ) in mental illness (bipolar disorder ( Wagner-Skacel et al, 2020 ; Ortelbach et al, 2022 ); eating disorders ( Rohde et al, 2019 ); personality disorders ( Zimmermann et al, 2014 ); major depressive disorder ( Zeeck et al, 2020 ) as well as cancer ( Wynn, 2010 ; Di Mattei et al, 2018 ) and chronic physical illness ( Leichter and Dreelin, 2005 ; Pollock-BarZiv and Davis, 2005 ; Moran et al, 2007 ; Lee et al, 2010 ). Only two studies have examined the influence of personality disorders on non-adherence in cardiovascular health to date ( Suárez-Bagnasco et al, 2015 ; Hall et al, 2019 ), indeed despite knowledge that personality disorders are an important risk factor for health-related matters such as physical functioning, role limitations, fatigue, and pain ( Powers and Oltmanns, 2012 ).…”
Section: Introductionmentioning
confidence: 99%